Wnt5a and Notum influence the temporal dynamics of cartilaginous mesenchymal condensations in developing trachea - Bottasso-Arias, Natalia; Mohanakrishnan, Megha; Trovillion, Sarah; Burra, Kaulini; Russell, Nicholas X.; Wu, Yixin; Xu, Yan; Sinner, Debora (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe trachea is essential for proper airflow to the lungs for gas exchange. Frequent congenital tracheal malformations affect the cartilage, causing the collapse of the central airway during the respiratory cycle. We have shown that Notum, a Wnt ligand de-acylase that attenuates the canonical branch of the Wnt signaling pathway, is necessary for cartilaginous mesenchymal condensations. In Notum deficient tracheas, chondrogenesis is delayed, and the tracheal lumen is narrowed. It is unknown if Notum attenuates non-canonical Wnt signaling. We observed premature tracheal chondrogenesis after mesenchymal deletion of the non-canonical Wnt5a ligand. We hypothesize that Notum and Wnt5a are required to mediate the timely formation of mesenchymal condensations, giving rise to the tracheal cartilage.Methods/ResultsEx vivo culture of tracheal tissue shows that chemical inhibition of the Wnt non-canonical pathway promotes earlier condensations, while Notum inhibition presents delayed condensations. Furthermore, non-canonical Wnt induction prevents the formation of cartilaginous mesenchymal condensations. On the other hand, cell-cell interactions among chondroblasts increase in the absence of mesenchymal Wnt5a. By performing an unbiased analysis of the gene expression in Wnt5a and Notum deficient tracheas, we detect that by E11.5, mRNA of genes essential for chondrogenesis and extracellular matrix formation are upregulated in Wnt5a mutants. The expression profile supports the premature and delayed chondrogenesis observed in Wnt5a and Notum deficient tracheas, respectively.ConclusionWe conclude that Notum and Wnt5a are necessary for proper tracheal cartilage patterning by coordinating timely chondrogenesis. Thus, these studies shed light on molecular mechanisms underlying congenital anomalies of the trachea.